en - Pongmasangka, Nico Linggi; Malik, Anis Rohmana; Erwandi, Dadan (Program Studi Magister Ergonomi Fisiologi Kerja Pascasarjana Universitas Udayana Denpasar Bekerjasama dengan Perhimpunan Ergonomi Indonesia (PEI), 2022)
Psychosocial risk factors can be stressors that have an impact on increasing work stress cases in a workplace. These risk factors cause various kinds of problems in workers such as occupational diseases and work accidents. One of the psychosocial measurement models in the workplace is the Copenhagen Psychosocial Questionnaire (COPSOQ) II. The sampling technique in this study used the Exhaustive Sampling Technique which was carried out on October 25 - 28, 2021 at PT. XYZ the number of samples is 34 workers. The results of this study found that the percentages were almost balanced between the good and bad categories, namely